BORON PREPARATIONS IN PSYCHIATRY AND NEUROLOGY: THEIR RISE, FALL AND RENEWED INTEREST - R. A. Bekker; Yu. V. Bykov (Acta Biomedica Scientifica, 2018)
The use of boron preparations (borax and boric acid) in medicine began long before their isolation in pure form. The mineral water of  boron-containing sources has been historically used to treat skin  diseases, to wash eyes, to disinfect wounds, etc. Also, what is of  interest in the context of this article, boron-containing waters were  used as calming, anti- anxiety, anticonvulsant and sleep-promoting  remedy. In 1777, boric acid was first isolated from the mineral water of a healing spring source in Florence. Historically, first name  of this compound was sal sedativum (“soothing salt”). However, the  discovery of boron toxicity led to the cessation of its internal use. In  recent decades, it has been found that boron is a microelement  necessary for many metabolic processes in the body. It affects  memory, cognitive functions, anxiety level, sleep, mood, regulates  calcium and magnesium exchange, metabolism of vitamin D and sex  steroids. It has been shown that some cases of treatment  resistance to standard therapy, for example in epilepsy, anxiety and depression, are related to boron deficiency. In this regard,  interest in the use of boron preparations in psychiatry and neurology, but in much smaller doses and on new scientific grounds, flared up again.